African swine fever virus does not express viral microRNAs in experimentally infected pigs - Fernando Núñez-Hernández; Gonzalo Vera; Armand Sánchez; Fernando Rodríguez; José I. Núñez (BMC Veterinary Research, 2018)
Abstract Background African swine fever virus (ASFV) is the etiological agent of African swine fever (ASF), a re-expanding devastating and highly lethal hemorrhagic viral disease. microRNAs (miRNAs) are a new class of small non-coding RNAs that regulate gene expression post-transcriptionally. The discovery of virus specific miRNAs has increased both in number and importance in the past few years. We have recently described the differential expression of several porcine miRNAs during in vivo infection with attenuated and virulent ASFV strains. Here, we have extended these studies trying to identify the presence of viral miRNAs encoded by ASFV in an in vivo infection in pigs. Results Sixteen small RNA libraries were analyzed from spleen and submandibular lymph nodes obtained from eight pigs, seven infected with either the virulent E75 ASFV strain or its attenuated counterpart E75CV1, or from pigs surviving E75CV1-infection and challenged with BA71 (heterologous challenge) and one non infected as negative control. Samples were recovered at different times post-infection. Libraries were analyzed by next-generation sequencing. Some viral miRNA candidates were initially identified, which did not correspond to porcine miRNAs. Further structural analyses were carried out in order to confirm if they met the conformational requirements to be considered a viral miRNA. Conclusions The analysis of sixteen small RNA libraries prepared from two different tissues obtained from pigs experimentally infected with E75, E75CV1 or with E75CV1 plus BA71, revealed the presence of six potential miRNA sequences but none of them met the requirements to be considered as viral miRNAs. Thus, we can conclude that ASFV does not express miRNAs in vivo, at least under the experimental conditions described here.